Approaches to studying abroad in Brazil and their effects on language learning and intercultural contact. (April 2021) - Diniz, Gabriela Loires; Noels, Kimberly A.
Abstract: Even though student mobility is increasingly frequent, the predominant direction is mainly from countries considered peripheral to those that have more economic and political representation (Altbach, 2004; OECD, 2015). This study investigated the reasons why students go to Brazil, the composition of their social networks, and their implications for learning Portuguese as a foreign language. This research had a mixed methods longitudinal design, in which 98 participants completed two questionnaires (i.e. in August and November 2016). A thematic analysis of the reasons that participants presented for going to Brazil resulted in three general "approaches": Actors, interested in idiosyncrasies of studying in Brazil; Observers, interested in having an experience abroad; and Riders, who had Brazil as a convenient choice. This classification not only predicted Portuguese language levels, but was related to participants' home countries, supporting an articulation of SA in terms of core-periphery relations (Wallerstein, 2004).